Combination of inclusive top-quark pair production cross-section measurements using ATLAS and CMS data at √s=7 and 8 TeV - Aad, Georges; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Rodriguez Bosca, Sergi; et al. (Journal of high energy physics, 2023)
A combination of measurements of the inclusive top-quark pair production cross-section performed by ATLAS and CMS in proton-proton collisions at centre-of-mass energies of 7 and 8 TeV at the LHC is presented. The cross-sections are obtained using top-quark pair decays with an opposite-charge electron-muon pair in the final state and with data corresponding to an integrated luminosity of about 5 fb−1 at √s = 7 TeV and about 20 fb−1 at √s = 8 TeV for each experiment. The combined cross-sections are determined to be 178.5 ± 4.7 pb at √s = 7 TeV and $$ {243.3}_{-5.9}^{+6.0} $$pb at √s = 8 TeV with a correlation of 0.41, using a reference top-quark mass value of 172.5 GeV. The ratio of the combined cross-sections is determined to be R8/7 = 1.363 ± 0.032. The combined measured cross-sections and their ratio agree well with theory calculations using several parton distribution function (PDF) sets. The values of the top-quark pole mass (with the strong coupling fixed at 0.118) and the strong coupling (with the top-quark pole mass fixed at 172.5 GeV) are extracted from the combined results by fitting a next-to-next-to-leading-order plus next-to-next-to-leading-log QCD prediction to the measurements. Using a version of the NNPDF3.1 PDF set containing no top-quark measurements, the results obtained are {m}_t^{pole}={173.4}_{-2.0}^{+1.8} $$GeV and $$ α_{s}\left({m}_Z\right)={0.1170}_{-0.0018}^{+0.0021}.
Veröffentlicht: 27. Juli 2023
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
*ATLAS collaboration: G. Aad, F. Bartels, F.L. Castillo, M.M. Czurylo, M. Dunford, S. Franchino, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und sehr viele weitere Personen]
Gesehen am 17.05.2024